Adaptive dose‐response studies to establish proof‐of‐concept in learning‐phase clinical trials. Issue 1 (4th October 2021) - Ma, Shiyang; McDermott, Michael P.
Abstract: In learning‐phase clinical trials in drug development, adaptive designs can be efficient and highly informative when used appropriately. In this article, we extend the multiple comparison procedures with modeling techniques (MCP‐Mod) procedure with generalized multiple contrast tests (GMCTs) to two‐stage adaptive designs for establishing proof‐of‐concept. The results of an interim analysis of first‐stage data are used to adapt the candidate dose‐response models and the dosages studied in the second stage. GMCTs are used in both stages to obtain stage‐wise p ‐values, which are then combined to determine an overall p ‐value. An alternative approach is also considered that combines the t ‐statistics across stages, employing the conditional rejection probability principle to preserve the Type I error probability. Simulation studies demonstrate that the adaptive designs are advantageous compared to the corresponding tests in a nonadaptive design if the selection of the candidate set of dose‐response models is not well informed by evidence from preclinical and early‐phase studies.